2000
DOI: 10.1046/j.1365-2516.2000.00443.x
|View full text |Cite
|
Sign up to set email alerts
|

Total joint arthroplasty in haemophilia

Abstract: In severely affected haemophilic patients arthropathy is a common problem which can lead to considerable pain and functional deficit. Surgical management, including total joint arthroplasty, can be undertaken if conservative management fails. A search of the literature showed that a number of studies describing the use of total knee arthroplasty (TKA) and total hip arthroplasty (THA) in haemophilia have been published, whereas shoulder, elbow and ankle arthroplasties are confined to case reports. This paper re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 42 publications
2
56
0
Order By: Relevance
“…Kelley et al reported in a multicentre trial on 34 hip arthroplasties in 28 years [12]. Total hip arthroplasty is less common than total knee arthroplasty [2,16]. The first reported arthroplasty of the hip in a haemophiliac patient was in 1967.…”
Section: Discussionmentioning
confidence: 99%
“…Kelley et al reported in a multicentre trial on 34 hip arthroplasties in 28 years [12]. Total hip arthroplasty is less common than total knee arthroplasty [2,16]. The first reported arthroplasty of the hip in a haemophiliac patient was in 1967.…”
Section: Discussionmentioning
confidence: 99%
“…Over time, advances in orthopaedic surgery and postoperative care have improved the outcome of TKR (Legroux-Gerot et al, 2003). Pain relief can be achieved in the vast majority of patients who undergo TKR, but improvements in postoperative ROM are more variable (Small et al, 1983;Beeton et al, 2000;Legroux-Gerot et al, 2003). Factors which may influence the ROM outcome include soft tissue contracture, stage of joint deterioration, type of prothesis, and postoperative mobilisation (use of a continuous passive motion machine or manipulation under anaesthesia) (Beeton et al, 2000).…”
Section: Joint Arthroplastymentioning
confidence: 99%
“…Pain relief can be achieved in the vast majority of patients who undergo TKR, but improvements in postoperative ROM are more variable (Small et al, 1983;Beeton et al, 2000;Legroux-Gerot et al, 2003). Factors which may influence the ROM outcome include soft tissue contracture, stage of joint deterioration, type of prothesis, and postoperative mobilisation (use of a continuous passive motion machine or manipulation under anaesthesia) (Beeton et al, 2000). Patients whose ROM does not increase may nonetheless experience improved functional mobility as a result of improvement in flexion contracture (Beeton et al, 2000).…”
Section: Joint Arthroplastymentioning
confidence: 99%
“…The general surgical principles are the same but tissue handling must be careful with particular attention paid to securing haemostasis [13,20]. The total joint replacement surgery is technically demanding, and complications are commonly described, particularly of the hip and knee [11]. There are many studies that demonstrated the outcome after total knee arthroplasty, because the knees are one of the targets joints in people with haemophilia [11].…”
Section: Discussionmentioning
confidence: 99%
“…Radiosynovierthesis, arthroscopic and open synovectomy, reduction of the osteophites and removing of loose bodies, arthroplasty and arthrodesis are the main surgical options for the chronic haemophilic arthropathy [11]. Total joint replacement is used more often on knee and hip joints that may improve the quality of life of these patients [11,12]. The postoperative rehabilitation is crucial for better outcome of these patients [13].…”
Section: Introductionmentioning
confidence: 99%